Accessibility and materialization of firm innovation - Jia, Ning; Tian, Xuan (Journal of Corporate Finance, 2018)
We examine the effect of a firm's accessibility to the United States Patent and Trademark Office (USPTO), captured by the firm's distance to it, on the materialization of the firm's innovation output. An increase in a firm's distance to the USPTO results in a longer time-to-patent-grant and a reduction in the quantity of patents owned. Accessibility is important for a firm's exploratory, but not for exploitative, innovation activity. The relation is more pronounced for first-time patent applicants, firms with a larger degree of information asymmetry, and before the launch of an electronic filing system. Finally, we show that market reacts positively to the opening of USPTO regional offices for innovation-intensive firms that enjoy a shorter distance to the USPTO, and that the contribution of a firm's patent portfolio to its equity value is larger when the firm is located closer to the USPTO. Our study demonstrates one strategy that firms can use to facilitate the materialization of their innovation outcomes, and highlights the importance of accessibility in fostering an effective innovation ecosystem.